Āyah al-Wasṭīyah: Dirāsah Dalālah Iḥtimālīyah - Pallawagau, Baso; Bugis, Manal (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2023)
Moderation is one of the most popular-discussed themes lately. Therefore, this study aims to reveal the meaning of probability in the moderation verse through qualitative research with descriptive-interpretative characteristics to describe opinions and ideas as well as to verify and interpret the data contained in the moderation verse. Obviously, this research is part of library research with a language and semantic approach. Methods of data collection through library research, editing, organizing, finding and documentary. Data analysis through deductive, interpretive, and comparative techniques. The results of the study show that the word (al wasth) has a meaning: a name between two sides, honesty and justice (al-'adl wa al 'iada), the meaning of choice (al khiyar), moderate, and balance. Al Wasth is between excess and negligence (al-irath wa al tafrith), moderate in faith and belief, moderate in the needs of the soul and body, and moderate in spiritual and material matters. The causes for the occurrence of probability meanings in words (al wasth) include: verbal association (polysemy), integration of morphological formulas and changes in true meaning to metaphors. It is hoped that the results of this research will have advantages and benefits in deepening the unique language and diction of the Qur'an al-Karim and its deep connotations. This paper certainly supports the concept of religious moderation in Indonesia to tackle religious extremism and terrorism. Understanding the meaning of moderation will open opportunities for dialogue, openness and tolerance.